2012
DOI: 10.1007/s00256-012-1421-6
|View full text |Cite
|
Sign up to set email alerts
|

The reliability and validity of radiographic measurements for determining the three-dimensional position of the talus in varus and valgus osteoarthritic ankles

Abstract: ObjectiveTo assess the most accurate radiographic method to determine talar three-dimensional position in varus and valgus osteoarthritic ankles, we evaluated the reliability and validity of different radiographic measurements.Materials and methodsNine radiographic measurements were performed blindly on weight-bearing mortise, sagittal, and horizontal radiographs of 33 varus and 33 valgus feet (63 patients). Intra- and interobserver reliability was determined with the intraclass coefficient (ICC). Discriminant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 17 publications
0
41
2
1
Order By: Relevance
“…The mean of the foot angles in the present study were between the values reported in previous studies with radiographs [8,[31][32][33][34][35][36] and skin markers during midstance of gait [37]. The variation across subjects (indicated by the standard deviation in Table 2) was with 14.38 slightly higher than the approximately 108 reported in the literature [8,[31][32][33]35,37,38].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…The mean of the foot angles in the present study were between the values reported in previous studies with radiographs [8,[31][32][33][34][35][36] and skin markers during midstance of gait [37]. The variation across subjects (indicated by the standard deviation in Table 2) was with 14.38 slightly higher than the approximately 108 reported in the literature [8,[31][32][33]35,37,38].…”
Section: Discussioncontrasting
confidence: 49%
“…The variation across subjects (indicated by the standard deviation in Table 2) was with 14.38 slightly higher than the approximately 108 reported in the literature [8,[31][32][33]35,37,38]. The importance of the posture on foot angles can be indicated by the effect of the postures in relation to the variation of the foot angles across subjects (between subject standard deviation).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…5,14,27 The sagittal position of the talus was determined on the lateral view measuring the talocalcaneal inclination angle (TCI) and the tibial lateral surface angle (TLS). 14,23 The rotation of the talus was assessed on the AP foot view with the talometatarsal 1 angle (TMT1), endorotation of the talus related to the first metatarsal was defined as a positive value. 23 The hindfoot alignment was assessed measuring the calcaneus offset on the Saltzman view.…”
Section: Preoperative Assessmentmentioning
confidence: 99%
“…14,23 The rotation of the talus was assessed on the AP foot view with the talometatarsal 1 angle (TMT1), endorotation of the talus related to the first metatarsal was defined as a positive value. 23 The hindfoot alignment was assessed measuring the calcaneus offset on the Saltzman view. 25 We published in a previous study the reliability and validity of these angles in a normal cohort (NC).…”
Section: Preoperative Assessmentmentioning
confidence: 99%